Lesotho : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1996)
This paper reviews economic developments in Lesotho during 1992-95. GDP growth accelerated from 2.4 percent in 1992 to 13.6 percent in 1994 before slowing to 12.6 percent in 1995. The expansion has largely reflected investment associated with the Lesotho Highlands Water Project (LHWP) as well as manufacturing for export. The LHWP alone accounted for 22.8 percent of gross national product (GNP) in 1995/96. Non-LHWP investment increased from 9.9 percent of GNP in 1988/89 to an estimated 23.4 percent in 1995/96.